How movement direction shapes the spatial representation of its effects: About the consequence of the ideomotor bidirectional association. Issue 7 (July 2019) - Lestage, Hélène; Camus, Thomas; Dru, Vincent; Brouillet, Thibaut
Ideomotor theories assume that action and perception share a common representational system in which a movement and its effect are equally represented and integrated by a bidirectional association. However, there is no mention of how this association leads to influence the representational content of each part. In this article, we investigated the influence of movement properties on the spatial representation of auditory effects. In line with the Action Constrains Theory of space perception, we suggest that changes in the movement direction leads to correlative changes in the spatial representation of the effect. In a pre-experiment, we replicated traditional ideomotor results with a response-effect (R-E) compatibility procedure. In two experiments, we used one condition of this procedure (i.e., the corresponding R-E mapping) to manipulate the movement properties associated to a non-spatialised effect. In the first experiment, the effect was associated with horizontal outward movements or with forward–backward movements. In the second experiment, we tested some alternative explanations for the results obtained in the first experiment. Globally, we showed that rightward movements led to localised auditory effect more on the right space than leftward movements and that backward movements led to localisation of the effect closer from the subjects than forward movements. In accordance with the Action Constrains Theory of space perception, these data suggest that movement shapes the spatial organisation of the effect representation.